2023
DOI: 10.1108/sef-12-2022-0555
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Russia-Ukraine war: evidence from DAX, ATX, and FTSEMIB

Abstract: Purpose The Russian invasion of Ukraine generated unprecedented panic in the European financial system. As expected, the European Union (EU) felt most of the negative effects of the war due to geographical proximity to Ukraine and energy dependence on Russia. This study aims to investigate the influence of Brent crude oil (BCO), Dutch Title Transfer Facility Natural Gas, and CBOE Volatility Index (VIX) on Deutscher Aktien Index (DAX), Austrian Traded Index (ATX) and Milano Indice di Borsa (FTSEMIB). The German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There is a study that has been carried out in early 2023 using global wheat price data from the same source as this study, which is FRED, but differs in terms of the study's goal. The study focuses on the relationship between the global market prices of four agricultural commodities, which are wheat, corn, barley, and sunflower oil, and the Russo-Ukrainian conflict, which involves food security issues around the world [26]. The methods they have used to study the relationship between all the variables are the VAR impulse response function, variance decomposition, Granger causality test, and vector error correction.…”
Section: Literature Research On Global Wheat Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a study that has been carried out in early 2023 using global wheat price data from the same source as this study, which is FRED, but differs in terms of the study's goal. The study focuses on the relationship between the global market prices of four agricultural commodities, which are wheat, corn, barley, and sunflower oil, and the Russo-Ukrainian conflict, which involves food security issues around the world [26]. The methods they have used to study the relationship between all the variables are the VAR impulse response function, variance decomposition, Granger causality test, and vector error correction.…”
Section: Literature Research On Global Wheat Pricesmentioning
confidence: 99%
“…The methods they have used to study the relationship between all the variables are the VAR impulse response function, variance decomposition, Granger causality test, and vector error correction. An additional purpose has also been implemented in the same research paper by implementing 10-month-ahead forecasting using vector autoregressive (VAR) and vector error correction (VECM) for all four agricultural commodities [26]. Another study on the price of wheat has also been carried out, but the price study is specific to a district in Pakistan, namely Faisalabad, Gujaranwala, and Multan, by implementing forecasting using Bagging Tree, GPR, Autoregressive Integrated Moving Average (ARIMA), and advanced neural network architecture Long Short-Term Memory (LSTM) networks [27].…”
Section: Literature Research On Global Wheat Pricesmentioning
confidence: 99%
“…The outcomes demonstrated that increasing DETRI lowers emissions. In addition to these studies, the recent literature asserted that enhancement in ecological innovation, energy investment, renewable sources, green growth and institutional quality are the substantial measures of environmental recovery (Bashir et al , 2023; Cai et al , 2022; Aliu et al , 2023; Gu et al. , 2023; Jiang et al , 2022; Batten et al , 2018; Luan et al , 2022; Shahzad et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One key factor driving this disruption is the surge in oil prices, directly impacting production costs and consequently affecting firms' financial performance. Energy prices, particularly oil and gas prices, significantly influence the global economy [17]. This confluence of factors makes it increasingly difficult for firms to achieve the financial performance necessary to satisfy their shareholders and stakeholders.…”
Section: Introductionmentioning
confidence: 99%